Proyecto de inversión para la comercialización de una revista nutricional en la ciudad de Guayaquil para la empresa “revistas s.a. - Gonzalez, Andrés (2009)
This work will allow us to know bad eating habits bring on chronic diseases that deteriorate people’s quality of life. In a certain way, these habits have been developed due to the aggressive marketing of the factories of processed food but specifically for the misinformation about the nutrition facts of its food. Nowadays not only viral diseases can cause harm. There are many other new eating disorders that have appeared as a result of this lifestyle that has made people face daily consequences of some degenerative diseases that lead to take into consideration the importance of good nutrition. For this purpose it is required that some media furnish reliable, updated, balanced, useful and timely information about how to obtain a good nutrition. It is because of this that we offer the community a smart publication that contributes to the consciousness and education of people about nutrition facts. It has been considered the fact to focus on the importance of right nutrition because here, particularly in Guayaquil, eating habits are not the best. Its first part involves general aspects of the companies in order to know its real situation. The second part will determine the necessity on behalf of the market. The third part shows information obtained through surveys taken directly from readers and one sample of possible sponsor companies. The fourth part will define the strategies to follow in order to achieve a high profit considering the reading of the magazine. And finally we have the last part that includes conclusions and recommendations regarding to the results obtained in our analysis.